Multi-template polymerase chain reaction - Kalle, Elena; Kubista, Mikael; Rensing, Christopher (Biomolecular detection and quantification, 2014)
PCR is a formidable and potent technology that serves as an indispensable tool in a wide range of biological disciplines. However, due to the ease of use and often lack of rigorous standards many PCR applications can lead to highly variable, inaccurate, and ultimately meaningless results. Thus, rigorous method validation must precede its broad adoption to any new application. Multi-template samples possess particular features, which make their PCR analysis prone to artifacts and biases: multiple homologous templates present in copy numbers that vary within several orders of magnitude. Such conditions are a breeding ground for chimeras and heteroduplexes. Differences in template amplification efficiencies and template competition for reaction compounds undermine correct preservation of the original template ratio. In addition, the presence of inhibitors aggravates all of the above-mentioned problems. Inhibitors might also have ambivalent effects on the different templates within the same sample. Yet, no standard approaches exist for monitoring inhibitory effects in multitemplate PCR, which is crucial for establishing compatibility between samples.
Keywords: SSCA, single strand conformation analysis; T-RFLP, terminal restriction fragment length polymorphism; DGGE, denaturing gradient gel electrophoresis; CDCE, constant denaturing capillary electrophoresis; Multi-template PCR; PAAG, polyacrylamide gel; Chimera; TGGE, temperature gradient gel electrophoresis; HPLC, high-performance liquid chromatography; DHPLC, denaturing high-performance liquid chromatography